Proviniência sedimentar e estratigrafia das formações Carrancas e Lagoa Formosa e a evolução do Grupo Bambuí (635-570 Ma) em Minas Gerais - Gabriel Jube Uhlein (2014)
Within the late Neoproterozoic (~635-570 Ma) Bambuí Group stratigraphy, the Carrancas and Lagoa Formosa formations had their stratigraphy and sedimentary provenance studied aiming to contribute for an improved geological evolution comprehension of both unities, as well as the Bambuí Group in the state of Minas Gerais. The Carrancas Formation represents the base of the southeast Bambuí Group, being characterized by conglomerates, siltstones, rhythmites, black shales, sandstones and sparse dolostones filling isolated channels carved into the Archean-Paleoproterozoic basement of the São Francisco Craton. Detrital zircons feature U-Pb ages between 2.1-3.3 Ga, meanwhile the Sm-Nd isotopic system shows model ages around 1.7-2.9 Ga and Nd(630Ma) varying from -22 to -7. Carbon and oxygen isotopic data from dolostones clasts within ortoconglomerates show provenance from dolostones layers with high 13C data from the Carrancas Formation itself. The Carrancas Formation exhibit variable provenance patterns with strong influence of the local basement along with less contribution of younger terranes. The important lateral provenance variation corroborates with isolated basins filling model. In this context, uplifts and subsidences of the cratonic basement may have acted as triggers for sinsedimentary faults, with generation of local depocenters and sub-basins and consequently exposition of early deposited sediments. The sedimentary facies of the Carrancas Formation are interpreted as gravitational fluxes products deposited inside isolated channels carved into the southern cratonic basement and being controlled by basin-edge faulting, without glacial influence. The partial isolation of these channels to the open sea favored the organic matter accumulation, as suggested by the black shales intercalations and by the dolostones layers with high 13C values. The Lagoa Formosa Formation outcrops at the southwestern margin of the Bambuí Group, near the limit with the Brasília fold belt. The mainly sedimentary facies are diamictite, ortonclomerate, siltstone, sandstone, and subordinate jaspilite and carbonate, all formed in submarine fan depositional setting. Detrital zircons U-Pb ages feature two groups of ages, one around 590 Ma and another between 1.0 and 3.0 Ga. This data, along with carbon and oxygen isotopic data from dolostone clasts, suggest a sedimentary provenance from metasedimentary pre-orogenic sequences and post-tectonic granitic intrusions within the Brasília fold belt. Sm-Nd data on pelites and diamictite matrix, along with the occurrence of mafic rocks clasts within ortoconglomerates, indicate a significantly contribution of mafic rocks and terranes with younger Nd isotopic evolution. Probably, the Goiás Magmatic Arc contributed with important Nd isotopic material and mafic clasts, but with little quantities of detrital zircons. The occurrence of jaspilites also corroborates with wide erosion of mafic substrate, besides representing specific hydrogeochemistry conditions achieved by the deposicional zone of the Lagoa Formosa Formation. The maximum depositional age constrained by ca.590 Ma suggests a deposition during relative tectonic quiescence of the Brasília fold belt, after the deformational and metamorphic peak and before the late position of external nappes, which thrust over rocks of the Bambuí Group (ca.590-576 Ma). Intraformational diamictitos can be interpreted as incised valleys filling deposited toward the top of the Lagoa Formosa Formation, indicating a forced regression regime. Progradational relationship is also exposed on the transition of the Serra da Saudade Formation to the Três Marias Formation, but influenced by a normal regression regime, with pelites grading to delta-front sigmoidal sandstones. Forced regression on the edge of the basin and normal regression on its central part is explained by uplifts of the foredeep depozone of foreland basins during tectonic quiescence and off-loading of the thrust fronts.